2010
DOI: 10.2190/de.40.3.c
|View full text |Cite
|
Sign up to set email alerts
|

Risky Alcohol Use, Peer and Family Relationships and Legal Involvement in Adolescents with Antisocial Problems

Abstract: The aim of the study was to examine risk and vulnerability factors contributing to problems with alcohol use in adolescence. Data relating to seven life areas (medical status, school status, social relationships, family background and relationships, psychological functioning, legal involvement, and alcohol use) was gathered using the ADAD (Adolescent Drug Abuse Diagnosis) interview. A total of 1163 Swedish adolescents (809 boys and 354 girls) between the ages of 12 and 20 years old were interviewed. All had an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
0
8
0
4
Order By: Relevance
“…Many studies have found strong associations between the engagement of peers and the engagement of the adolescent in risky or deviant behaviors. (4244) Not only do these studies support the powerful influence of peers on an adolescent’s behaviors, the literature also suggests that in some cases, the strength of peer influence may in fact reverse the protective effects of positive family and school-based relationships. (45)…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many studies have found strong associations between the engagement of peers and the engagement of the adolescent in risky or deviant behaviors. (4244) Not only do these studies support the powerful influence of peers on an adolescent’s behaviors, the literature also suggests that in some cases, the strength of peer influence may in fact reverse the protective effects of positive family and school-based relationships. (45)…”
Section: Discussionmentioning
confidence: 97%
“…(46) Studies from the U.S. and other countries have found that good family relationships including support, cohesion, and closeness to parents, protected against engagement in sexual behaviors and alcohol use. (44, 45, 4749) Parental monitoring has also been strongly associated with reduced levels of engagement in risky behaviors. (50)…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents with a foreign background are found to be a risk group when accompanied by a low socioeconomic status of the parents (beckman & Hagquist 2010) and this is also the case with adolescents living with a single parent of low income (Hagquist 2010;Jerden et al 2011;ringback weitoft et al 2008). Parental abuse and adolescent lack of support and trust in family relationships are risk factors for negative mental health (Ybrandt 2010;Ybrandt & armelius 2010). In a recent study, Swedish adolescents reported that they consider the family to be the most important determinant for their mental health (JoHansson et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from resulting in damage to the developing brain, excessive use of alcohol during adolescence has been associated with social problems, increased risk for physical and mental harm, and delinquency [4][5][6][7]. High consumption of alcohol in early adolescence is also associated with alcohol problems in adulthood [8,9].…”
mentioning
confidence: 99%